Pre-clinical development of a novel CD3-CD123 bispecific T-cell engager using cross-over dual-variable domain (CODV) format for acute myeloid leukemia (AML) treatment. (1st January 2021) - Bonnevaux, Hélène; Guerif, Stephane; Albrecht, Jana; Jouannot, Erwan; De Gallier, Thibaud; Beil, Christian; Lange, Christian; Leuschner, Wulf Dirk; Schneider, Marion; Lemoine, Cendrine; Caron, Anne; Amara, Céline; et al.
ABSTRACT: Novel therapies are needed for effective treatment of AML. In the relapsed setting, prognosis is very poor despite salvage treatment with chemotherapy. Evidence suggests that leukemic stem cells (LSCs) cause relapse. The cell surface receptor CD123 is highly expressed in blast cells and LSCs from AML patients and is a potential therapeutic target. CD123 cross-over dual-variable domain T-cell engager (CD123-CODV-TCE) is a bispecific antibody with an innovative format. One arm targets the CD3εδ subunit of T-cell co-receptors on the surface of T cells, while the other targets CD123 on malignant cells, leading to cell-specific cytotoxic activity. Here, we describe the preclinical activity of CD123-CODV-TCE. CD123-CODV-TCE effectively binds to human and cynomolgus monkey CD3 and CD123 and is a highly potent T-cell engager. It mediates T-cell activation and T-cell-directed killing of AML cells in vitro. In vivo, CD123-CODV-TCE suppresses AML tumor growth in leukemia xenograft mouse models, where it achieves an effective half-life of 3.2 days, which is a significantly longer half-life compared to other bispecific antibodies with no associated Fc fragment. The in vitro safety profile is as expected for compounds with similar modes of action. These results suggest that CD123-CODV-TCE may be a promising therapy for patients with relapsed/refractory AML.